Antioxidant activity of Agaricus sp. mushrooms by chemical, biochemical and electrochemical assays - Barros, Lillian; Falcão, Soraia; Baptista, Paula; Freire, Cristina; Vilas-Boas, Miguel; Ferreira, Isabel C.F.R. (Food chemistry, 2008)
The antioxidant activity of five Agaricus sp. mushrooms was screened through chemical, biochemical and electrochemical techniques. The chemical assays allowed an evaluation of their reducing power and radical scavenging activity, while biochemical assays evaluated the lipid peroxidation inhibition capacity, using erythrocytes and brain cells as models; the electrochemical characterization of the mushrooms extracts were performed by cyclic voltammetry and differential pulse voltammetry. All the species proved to have antioxidant activity and particularly, by the electrochemical techniques, it has been shown that mushroom extracts revealed similar electrochemical responses, suggesting similar electroactive chemical composition, and oxidation potentials more positive than those of the standards (ascorbic and gallic acids). Agaricus silvaticus was the most efficient species presenting the lowest EC 50 values in the chemical and biochemical assays, and the highest “antioxidant power” in the electrochemical assays.